Chapter Competenze lessicali in italiano L2: gli eventi di moto in testi narrativi - VALENTINI, Ada (Strumenti per la didattica e la ricerca, 2021)
This paper deals with a case of lexical cross-linguistic influence from a source language, known as conceptual transfer. In particular, narratives in Italian L2 produced by different L1 learners are examined. The theoretical framework adopted is lexical typology as developed by L. Talmy, according to which languages fall into two types as to how they encode motion events: The so-called verb-framed languages would tend to lexicalize the semantic component of the Path (eg the movement from inside to outside or vice versa) in the verb (eg It. uscire "to go out"); the satellite-framed languages preferentially encode the Path component outside the verb (eg in Eng. in the satellite out, as in "The boy ran out"). The preferences adopted in each L1 are supposed to influence production in L2. The presentation of the data in Italian L2 allows us to observe the subtle role that the L1s play in this lexical domain and to recommend giving attention to typological differences between L2 and L1 in the classroom.